2019
DOI: 10.3390/ma12132172
|View full text |Cite
|
Sign up to set email alerts
|

Hot Deformation Behavior and Microstructural Evolution of a Novel β-Solidifying Ti–43Al–3Mn–2Nb–0.1Y Alloy

Abstract: In this paper, the hot deformability and mechanical properties of a novel Mn- and Nb- containing TiAl alloy were studied systematically with the use of isothermal compression experiments. The results show that the alloy has low deformation resistance and a low activation energy (392 KJ/mol), suggesting that the alloy has good hot deformability. A processing map was established, which shows that the present alloy has a smaller instability region and wider hot working window compared with other TiAl alloys. Micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…However, their intrinsic brittleness has hindered their wider use. Thermal deformation is a suitable way to obtain a fine-grained microstructure, which is beneficial for the ductility of TiAl alloys [5,8]. Past research has confirmed that the hot workability of TiAl alloys can be significantly enhanced by the β phase with a disordered body-center cubic lattice at above 1150 °C [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, their intrinsic brittleness has hindered their wider use. Thermal deformation is a suitable way to obtain a fine-grained microstructure, which is beneficial for the ductility of TiAl alloys [5,8]. Past research has confirmed that the hot workability of TiAl alloys can be significantly enhanced by the β phase with a disordered body-center cubic lattice at above 1150 °C [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties and high-temperature deformability of a new TiAl alloy containing Nb and Mn were studied by Wu et al. [ 107 ]. It was deduced that the alloy had good hot deformability based on recorded low activation energy (392 kJ/mol) and low deformation resistance of the alloy.…”
Section: Effects Of Alloying Elements On Tial-based Alloysmentioning
confidence: 99%
“…As stated earlier, the β-solidifying TiAl-based alloys properties are extremely dependent on compositions, particularly the β-stabilizing elements in the alloy. The mechanical properties and high-temperature deformability of a new TiAl alloy containing Nb and Mn were studied by Wu et al [107]. It was deduced that the alloy had good hot deformability based on recorded low activation energy (392 kJ/mol) and low deformation resistance of the alloy.…”
Section: Phase Formation and Microstructural Stabilitymentioning
confidence: 99%